Peningkatan Kapasitas Industri Rumah Tangga melalui Edukasi Praktik Akuntansi Biaya dan Manajemen Keuangan pada Usaha Tempe dan Keripik Tempe - Susana Himawati; Kertati Sumekar; Supriyono; Noor Indah Rahmawati; Agung Subono (Muria Jurnal Layanan Masyarakat, 2026)
This article aims to provide practical education on basic cost accounting and financial management for tempeh home industries in Winong and Langse Villages, Pati Regency. The methodology includes SWOT surveys, production cost recording exercises, and basic financial management training using simple report simulations to establish organized accounting habits. Results indicate an improvement in participants' ability to calculate production costs accurately to determine a reasonable Cost of Goods Sold (COGS). Furthermore, participants have begun separating business and household finances while maintaining simple records of cash flow, assets, liabilities, and profit. Conclusions, limitations, and suggestions are also discussed.